Using cloud data to accelerate forensic investigations. (September 2015) - Rozanski, Shahaf
Abstract : Cloud data represents a virtual goldmine of potential evidence for forensic investigators. Together with mobile device data, cloud data sources often present the critical connections investigators need to solve crimes. However, there are a number of challenges that investigators face when it comes to data retrieval from the cloud.